Performance Investigation of 40 GB/s DWDM over Free Space Optical Communication System Using RZ Modulation Format. (10th February 2016) - Parkash, Sooraj; Sharma, Anurag; Singh, Harsukhpreet; Singh, Harjit Pal
Abstract : We successfully demonstrate 40 GB/s 8 channels' Dense Wavelength Division Multiplexing (DWDM) over free space optical (FSO) communication system. Each channel is transmitting 5 GB/s data rate in downstream separated by 0.8 nm (100 GHz) channel spacing with 1.8 GHz filter bandwidth. DWDM over FSO communication system is very effective in providing high data rate transmission with very low bit error rate (BER). The maximum reach of designed system is 4000 m without any compensation scheme. The simulation work reports minimum BER for Return-to-Zero (RZ) modulation format at different channels 1, 4, and 8 are found to be2.32 e - 17, 1.70 e - 16, and9.51 e - 15 at 4000 m distance, respectively. Sharp increase in BER occurs if data rate and distance increase up to 10 GB/s and 5000 m.